Recall Accuracy in Children: Age vs. Conceptual Thinking - Murnikov, Valeri; Kask, Kristjan (Frontiers in Psychology, 2021)
The aim of this study was to replicate an experiment by Kask, Ventsel, and Toomela (2019) using a different stimulus event. The present study examined the relationship between age, development of conceptual thinking, and responses to different question types in children and adults. Sixty-three children (aged 7–14) and 30 adults took part in an experiment in which they first participated in a live staged event, then, a week later, were interviewed about the event and tested using the Word Meaning Structure Test. Age and level of conceptual thinking were positively correlated in children. Compared to age, conceptual thinking ability better predicted children’s accurate free recall and inaccurate responses to specific option-posing questions, but not inaccurate responses to suggestive questions.